Case report: Hepatotoxicity and nephrotoxicity induced by methotrexate in a paediatric patient, what is the role of precision medicine in 2023? - El Masri, Ali El Rida; Tobler, Caroline; Willemijn, Breunis; Von Bueren, Andre O.; Ansari, Marc; Samer, Caroline Flora (Frontiers in Pharmacology, 2023)
Methotrexate is an immunosuppressant and chemotherapeutic agent used in the treatment of a range of autoimmune disorders and cancers. Its main serious adverse effects, bone marrow suppression and gastrointestinal complications, arise from its antimetabolite effect. Nevertheless, hepatotoxicity and nephrotoxicity are two widely described adverse effects of methotrexate. Its hepatotoxicity has been studied mainly in the low-dose, chronic setting, where patients are at risk of fibrosis/cirrhosis. Studies of acute hepatoxicity of high dose methotrexate, such as during chemotherapy, are scarce. We present the case of a 14-year-old patient who received high-dose methotrexate and subsequently developed acute fulminant liver failure and acute kidney injury. Genotyping of MTHFR (Methylene tetrahydrofolate reductase gene), ABCB1 (codes for P-glycoprotein, intestinal transport and biliary excretion), ABCG2 (codes for BCRP, intestinal transporter and renal excretion) and SLCO1B1 (codes for OATP1B1, hepatic transporter) identified variants in all the genes analysed that predicted a reduced rate of methotrexate elimination and thus may have contributed to the clinical situation of the patient. Precision medicine involving pharmacogenomic testing could potentially avoid such adverse drug effects.